2019
DOI: 10.1142/s1363919620500681
|View full text |Cite
|
Sign up to set email alerts
|

ENTREPRENEUR’S GENDER AND FIRM INNOVATION BREADTH: AN INSTITUTION-BASED VIEW OF SMEs IN AN EMERGING MARKET CONTEXT

Abstract: This study, at the intersection of gender, entrepreneurship and innovation, investigates the impact of women leadership (vis-a-vis men) on innovation by SMEs in an emerging economy context. Drawing from the institution-based view, we examine the moderating role of regional formal institutions and informal gender norms on the innovativeness of women-led SMEs in India. Using data obtained from the World Bank Enterprise Survey and World Value Survey, and deploying the Poisson regression method, we find that, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 78 publications
1
31
2
Order By: Relevance
“…et al , 2019). Though qualitative studies present a good description of the context in their study (Kothari, 2017; Zapalska et al , 2015), the use of culture or institutional explanations in quantitative studies are rarely region-specific, but for a few exceptions shown by Reutzel et al (2018), T.M. et al (2019) and Strohmeyer et al (2017).…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
See 4 more Smart Citations
“…et al , 2019). Though qualitative studies present a good description of the context in their study (Kothari, 2017; Zapalska et al , 2015), the use of culture or institutional explanations in quantitative studies are rarely region-specific, but for a few exceptions shown by Reutzel et al (2018), T.M. et al (2019) and Strohmeyer et al (2017).…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…On the other hand, some studies studied individual entrepreneurs. While studies such as Strohmeyer et al (2017) and Link and van Hasselt (2019) show a negative relationship between gender of the entrepreneur and innovation, studies such as Farooq et al (2019) andT.M. et al (2019) show that the gender of the entrepreneur has a positive influence on innovation.…”
Section: Gender and Firm Innovationmentioning
confidence: 98%
See 3 more Smart Citations